1979
DOI: 10.1073/pnas.76.11.5524
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation in the Escherichia coli tryptophan operon: role of RNA secondary structure involving the tryptophan codon region.

Abstract: The secondary structure of the terminated tip leader transcript from Escherichia coli was analyzed by RNase Ti partial digestion. Base-paired regions were recovered by nondenaturing gel electrophoresis and identified by denaturing gel electrophoresis and fingerprinting. The tandem tryptophan codons in the leader peptide coding region were found to be base paired with a more distal region of the transcript. This and other secondary structures that the tip leader RNA can form help explain the physiological respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
80
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 20 publications
5
80
0
Order By: Relevance
“…gene regulation | translational control | metabolism R NA structures fulfill important roles in the regulation of gene expression including the control of translational initiation, transcriptional termination, and alternative splicing (1)(2)(3)(4)(5). In many cases, an RNA conformational change is crucial to gene regulation since one RNA sequence may adopt alternate structures.…”
mentioning
confidence: 99%
“…gene regulation | translational control | metabolism R NA structures fulfill important roles in the regulation of gene expression including the control of translational initiation, transcriptional termination, and alternative splicing (1)(2)(3)(4)(5). In many cases, an RNA conformational change is crucial to gene regulation since one RNA sequence may adopt alternate structures.…”
mentioning
confidence: 99%
“…30 In essence, the choice between terminator and anti-terminator structures bridges the communication between the translation of the leader peptide and the transcription of operon genes in exchanging the message for the abundance of trp. 10,33 Dual regulatory systems for the operon expression When trp is abundant, the cell uses a repressive system to promote the synthesis of other amino acids in starvation; here, the trpR repressor operates on the transcription initiation whereas the attenuation operates on the progressing transcription. 10 The repression system targets the intracellular trp concentration which depends on the influx trp, the newly synthesised trp, and finally the consumption of trp for protein synthesis.…”
Section: Trp Operon Leadermentioning
confidence: 99%
“…Lee and Yanofsky (1977) concluded that the termination efficiency at the attenuator is correlated with the stability of an embedded secondary structure which is conserved between E. coli and Salmonnella typhimurium; the proposed structures agree with results of a partial RNase T1 digestion that exhibit digestion resistance in the distal portion of this transcript, i.e., where the structural features are located. 32 Thereafter, Oxender et al (1979) conducted structural probing with RNase T1 partial digestion followed by isolation of the comigrating pairing regions in a non-denaturing gel electrophoresis; the base-pairing regions were subsequently identified via denaturing gel electrophoresis and fingerprinting, based on which the two hairpins comprising the terminator structure were drawn. 33 Later on, the secondary structure of DNA template was ruled out as a contributor for this termination signal so the RNA structural features are the one causing the termination.…”
Section: Trp Operon Leadermentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of operons for the biosynthesis of amino acids like trp (10), his (1,2,7,8,11), pheA (12), leu (13), thr (14), and ilv (15,16) is regulated by transcription termination at the attenuator barrier. Active synthesis and translation of a small mRNA called leader RNA is an essential part of this regulatory mechanism (2,11,17,18).…”
mentioning
confidence: 99%